2009
DOI: 10.1002/ejlt.200800148
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic behavior of fatty acid derivatives for mass spectrometry on low‐polarity capillary columns

Abstract: The gas chromatographic properties of four derivatives of fatty acids (FA), namely fatty acid methyl esters, picolinyl esters, N-acyl pyrrolidides and 4,4-dimethyloxazoline derivatives, which contain various structural features (double bonds, branching, hydroxyl group) in their acyl chains have been compared on a low-polarity capillary column with a mass spectrometer as detector. Temperature programming rates yielding the highest resolution were optimized for each derivative by means of computer-assisted colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…A rather mild method was used for the synthesis of DMOX derivatives of FA (Svetashev 2011). It is known that ECL values of methyl esters, pyrrolidides, and DMOX derivatives of FA are similar on low-polarity GC columns (Dubois et al 2009). The comparison of GC chromatograms of N-acyl derivatives and methyl esters of 18:5n-3 showed that both pyrrolidine and DMOX derivatives chromatograms had one major peak.…”
Section: Fame Analysismentioning
confidence: 99%
“…A rather mild method was used for the synthesis of DMOX derivatives of FA (Svetashev 2011). It is known that ECL values of methyl esters, pyrrolidides, and DMOX derivatives of FA are similar on low-polarity GC columns (Dubois et al 2009). The comparison of GC chromatograms of N-acyl derivatives and methyl esters of 18:5n-3 showed that both pyrrolidine and DMOX derivatives chromatograms had one major peak.…”
Section: Fame Analysismentioning
confidence: 99%
“…However, the double‐bond positions cannot be determined by comparing the similarity between the mass spectrum and the library data. Conventionally, the derivatives such as pyrrolidide or picolinyl ester are used in determining the double‐bond positions of unsaturated fatty acid with GC/MS (Åkesson‐Nilsson & Wesén, ; Andersson, Heimermann, & Holman, ; Andersson & Holman, ; Christie, , ; Christie, Brechany, & Holman, ; Christie & Han, ; Destaillats & Angers, ; Dobson & Christie, ; Dubois, Barnathan, Gouygou, & Bergé, ; Dubois, Barthomeuf, & Bergé, ; Wretensjö, Svensson, & Christie, ). With the aforementioned method, the double‐bond positions can be determined by the difference of fragment ions in which cleavage occurs between the double‐bond carbons is 12u, and the difference of fragment ions in which cleavage occurs between the single‐bond carbons is 14u.…”
Section: Introductionmentioning
confidence: 99%
“…Some reported analysis procedures convert triglycerides into picolinyl esters, -acyl pyrrolidines, and DMOX derivatives (4,4-dimethyloxazoline) to enable detection by mass spectrometry. These derivatives are separated using a lowpolarity column because of its high thermal stability [18]. Gas chromatography-mass spectrometry (GC-MS) has been widely used for the structural analysis of FAs.…”
Section: Introductionmentioning
confidence: 99%